Determination of Sterol and Fatty Acid Compositions, Oxidative Stability, and Nutritional Value of Six Walnut (Juglans regia L.) Cultivars Grown in Portugal - Amaral, Joana S. (2008)
Six cultivars (Franquette, Marbot, Mayette, Mellanaise, Lara, and Parisienne) of walnuts (Juglans regia L.) were collected during the 2001 crop, from Bragança, Portugal. Chemical composition, including moisture, total oil content, crude protein, ash, carbohydrates, and nutritional value, was evaluated. Fat was the predominant component, ranging from 62.3 to 66.5%. Total oil was extracted and analyzed for fatty acids, sterols, oxidative stability, and peroxide value. Fatty acids and sterols were determined by gas-liquid chromatography coupled to a flame ionization detector. Eighteen fatty acids were quantified. Polyunsaturated fatty acids and, in particular, linoleic acid were predominant. â-Sitosterol, ¢5-avenasterol, and campesterol were the major sterols found. Differences were observed among the studied cultivars, especially in peroxide values and in the sterol profile.